Method for producing binder resin for toner
Patent Information
- Application Number
- JP2022064059
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-07
- Publication Date
- 2025-03-26
- Estimated Expiration
- 2042-04-07
AI Technical Summary
High molecular weight amorphous polyester resins provide excellent hot offset resistance but often compromise low-temperature fixability in toners.
A method involving the addition-polymerization of an addition-polymerizable monomer and an amphoteric monomer in the presence of a polymer with unsaturated bonds, followed by polycondensation, to create a binder resin with both high molecular weight and crosslinked segments, ensuring both hot offset resistance and low-temperature fixing properties.
The resulting binder resin achieves a balance between hot offset resistance and low-temperature fixability, enhancing the performance of toners in electrophotographic processes.
Abstract
Description
[Technical Field]
[0001] The present invention relates to a method for producing a binder resin for a toner used in developing a latent image formed in electrophotography, electrostatic recording, electrostatic printing, etc., and a method for producing a toner for developing an electrostatic image. [Background technology]
[0002] Patent Document 1 discloses an electrophotographic toner characterized by containing at least a binder resin having an unsaturated double bond, a reactive monomer, and a radical polymerization catalyst.
[0003] Patent Document 2 discloses a method for producing a toner, which includes the steps of: dispersing a polyester resin obtained by condensing a polyhydric alcohol and an unsaturated polycarboxylic acid in an aqueous medium to prepare a polyester resin particle dispersion; adding a vinyl polymerizable monomer and a radical polymerization initiator to the polyester resin particle dispersion and then subjecting the mixture to a radical polymerization reaction to prepare a dispersion of resin particles formed from a resin in which the vinyl polymerizable monomer has reacted with the polyester resin; and mixing resin particles formed from at least the resin in which the vinyl polymerizable monomer has reacted with the polyester resin with a dispersion of colorant particles, and aggregating the resin particles and colorant particles to form toner particles.
[0004] Patent Document 3 discloses a method for producing a binder resin for toner, which includes step (A) of subjecting an addition polymerization resin monomer containing styrene to an addition polymerization reaction, and step (B) of mixing the reaction mixture produced in step (A) with fumaric acid and / or maleic acid during and / or after step (A), wherein the amount of fumaric acid and / or maleic acid mixed in step (B) is 0.05 to 10 parts by weight per 100 parts by weight of the addition polymerization resin monomer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 8-30026 [Patent Document 2] Japanese Patent Application Laid-Open No. 2011-95736 [Patent Document 3] Japanese Patent Application Laid-Open No. 2005-350510 Summary of the Invention [Problem to be solved by the invention]
[0006] To ensure the hot offset resistance of the toner, a high molecular weight amorphous polyester resin is effective as a binder resin, but there is a concern that this may result in a deterioration in low temperature fixability.
[0007] The present invention relates to a method for producing a binder resin for toner that has excellent hot offset resistance and low-temperature fixability. [Means for solving the problem]
[0008] The present invention provides [1] A method for producing a binder resin for toner, in which a polycondensation resin segment and an addition polymerization resin segment are bonded via a bireactive monomer, comprising: a step A of addition-polymerizing an addition-polymerizable monomer and a bireactive monomer in the presence of a polymer (A) having an unsaturated bond; and a step B of polycondensing a polycondensation monomer containing a carboxylic acid component and an alcohol component, wherein the steps A and B are carried out in the same reaction vessel, and wherein the amount of the monomer having an unsaturated bond constituting the polymer (A) having an unsaturated bond is 5.0 × 10 relative to 1 g of the total amount of the addition-polymerizable monomer, the bireactive monomer, and the polycondensation monomer. -5 mmol or more 2.0 × 10 -2 mmol or less, and a method for producing a binder resin for toner; [2] A method for producing a toner for developing an electrostatic image, comprising: a step (I) of dispersing the toner binder resin obtained by the method according to [1] in an aqueous medium to obtain resin particles; and a step (II) of aggregating and fusing the resin particles to obtain toner particles. Regarding. [Effects of the Invention]
[0009] The binder resin for toner obtained by the method of the present invention exhibits the effect of providing toner with excellent hot offset resistance and low-temperature fixability. DETAILED DESCRIPTION OF THE INVENTION
[0010] The present invention has a major feature in that, when producing a binder resin for toner in which a polycondensation resin segment and an addition polymerization resin segment are bonded via a bireactive monomer, the step of addition-polymerizing an addition-polymerizable monomer and a bireactive monomer is carried out in the presence of a polymer (A) having a predetermined amount of unsaturated bonds. Although the details are unknown, it is presumed that the effects of the present invention are achieved by the following mechanism.
[0011] As mentioned above, high-molecular-weight amorphous polyesters are effective in ensuring hot offset resistance, but there is a concern that they may deteriorate low-temperature fixability. However, in the present invention, by addition-polymerizing an addition-polymerizable monomer and a bireactive monomer in the presence of a polymer (A) having a predetermined amount of unsaturated bonds, a portion of the polymer (A) having unsaturated bonds functions as a crosslinking element, and the unsaturated bonds of the polymer (A) bond to the addition-polymerization resin segment, a high-molecular-weight crosslinked material is produced that partially contains a resin component with an appropriate molecular weight that is excellent in low-temperature fixability while preventing gelation from spreading throughout the material. It is believed that this makes it possible to produce a binder resin that can achieve both low-temperature fixability and hot offset resistance.
[0012] In the present invention, the polymer (A) having an unsaturated bond is not particularly limited as long as it has an unsaturated bond, and examples thereof include polyester resins, composite resins having a polyester resin segment and a styrene-based resin segment, polyamide resins, vinyl resins such as styrene-based resins, epoxy resins, polycarbonate resins, and polyurethane resins. In the present invention, from the viewpoints of ease of compounding and achieving both low-temperature fixability and hot offset resistance, polyester resins or composite resins having a polyester resin segment and a styrene-based resin segment are preferred, and composite resins having a polyester resin segment and a styrene-based resin segment are more preferred.
[0013] The polyester resin is preferably a polycondensation product of an alcohol component and a carboxylic acid component, at least one of which contains a monomer having an unsaturated bond.
[0014] As the monomer having an unsaturated bond, an unsaturated aliphatic dicarboxylic acid compound is preferred from the viewpoint of reactivity with addition polymerizable monomers.
[0015] Examples of unsaturated aliphatic dicarboxylic acid compounds include fumaric acid, maleic acid, citraconic acid, mesaconic acid, 2-pentenedioic acid, itaconic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms, with fumaric acid or maleic acid being preferred. Therefore, the polymer (A) having an unsaturated bond preferably has a structural unit derived from at least one of fumaric acid and maleic acid.
[0016] The number of carbon atoms in the unsaturated aliphatic dicarboxylic acid compound is preferably 4 or more from the viewpoint of reactivity with addition-polymerizable monomers, and is preferably 10 or less, more preferably 8 or less, from the viewpoint of low-temperature fixability. In this specification, when the aliphatic dicarboxylic acid compound is an alkyl ester, the number of carbon atoms in the alkyl group is not included in the above carbon number.
[0017] The content of the unsaturated aliphatic dicarboxylic acid compound in the carboxylic acid component is preferably 2 mol % or more, more preferably 5 mol % or more, and preferably 80 mol % or less, more preferably 60 mol % or less.
[0018] Examples of other carboxylic acid components include saturated aliphatic dicarboxylic acid compounds, aromatic dicarboxylic acid compounds, and trivalent or higher carboxylic acid compounds.
[0019] Examples of saturated aliphatic dicarboxylic acid compounds include succinic acid, succinic acid derivatives substituted with a hydrocarbon group, adipic acid, sebacic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0020] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0021] Examples of the trivalent or higher carboxylic acid compound include trimellitic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0022] When a trivalent or higher carboxylic acid compound is contained from the viewpoint of increasing the softening point, the content of the trivalent or higher carboxylic acid compound in the carboxylic acid component is preferably 10 mol % or more, more preferably 20 mol % or more, and is preferably 50 mol % or less, more preferably 40 mol % or less.
[0023] The alcohol component preferably contains an alkylene oxide adduct of bisphenol A. Examples of the alkylene oxide adduct of bisphenol A include alkylene oxide adducts represented by the formula (I):
[0024] [ka]
[0025] (wherein OR and RO are oxyalkylene groups, R is an ethylene group and / or a propylene group, x and y are the average number of moles of alkylene oxide added and are each a positive number, and the sum of x and y is 1 or more, preferably 1.5 or more, and 16 or less, preferably 8 or less, more preferably 6 or less, and even more preferably 4 or less.) A compound represented by the following formula is preferred.
[0026] From the viewpoint of low-temperature fixability, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and even more preferably 100 mol%.
[0027] Examples of other alcohol components include aliphatic diols, bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, tri- or higher hydric alcohols such as trimethylolpropane, and the like.
[0028] The alcohol component may contain a monohydric alcohol, and the carboxylic acid component may contain a monocarboxylic acid compound, as appropriate.
[0029] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component (COOH groups / OH groups) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.75 or more, and is preferably 1.2 or less, more preferably 1.15 or less.
[0030] The polyester resin can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature of preferably 130°C or higher, more preferably 170°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.
[0031] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanolamine. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, per 100 parts by mass of the alcohol component and the carboxylic acid component combined. Examples of the esterification promoter include gallic acid. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, per 100 parts by mass of the alcohol component and the carboxylic acid component combined. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0032] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like, by the methods described in JP-A Nos. 11-133668, 10-239903, and 8-20636. Among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.
[0033] In the composite resin containing the polyester resin segment and the styrene-based resin segment, the raw material monomers of the polyester resin constituting the polyester resin segment are the same as the raw material monomers of the polyester resin.
[0034] The styrene-based resin segment is an addition polymer of raw material monomers containing at least styrene or a styrene derivative such as α-methylstyrene or vinyltoluene (hereinafter, styrene and styrene derivatives are collectively referred to as "styrene compounds").
[0035] The content of the styrene compound, preferably styrene, in the raw material monomers of the styrene-based resin segment is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, from the viewpoint of storage stability, and is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 90% by mass or less, from the viewpoint of low-temperature fixability.
[0036] The styrene-based resin segment may also contain, as a raw material monomer, a (meth)acrylic acid alkyl ester having an alkyl group with 7 or more carbon atoms. Examples of (meth)acrylic acid alkyl esters include 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, and (iso)stearyl (meth)acrylate. It is preferable to use one or more of these. In this specification, "(iso)" means both the presence and absence of this group, and indicates normal when this group is not present. Furthermore, "(meth)acrylic acid" refers to acrylic acid, methacrylic acid, or both.
[0037] From the viewpoint of improving the low-temperature fixability of the toner, the number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester used as a raw material monomer for the styrene-based resin segment is preferably 7 or more, more preferably 8 or more, and preferably 12 or less, more preferably 10 or less. The number of carbon atoms in the alkyl ester refers to the number of carbon atoms derived from the alcohol component constituting the ester.
[0038] The raw material monomers for the styrene-based resin segment may include raw material monomers other than styrene compounds and (meth)acrylic acid alkyl esters, for example, ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; ethylenic monocarboxylic acid esters such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone.
[0039] The addition polymerization reaction of raw material monomers for the styrene-based resin segment can be carried out by a conventional method in the presence of a polymerization initiator such as dibutyl peroxide or dicumyl peroxide, a chain transfer agent, a crosslinking agent, or the like, in the presence of an organic solvent or in the absence of a solvent. The temperature conditions are preferably 110°C or higher, more preferably 140°C or higher, and preferably 200°C or lower, more preferably 170°C or lower.
[0040] When an organic solvent is used in the addition polymerization reaction, xylene, toluene, methyl ethyl ketone, acetone, etc. can be used. The amount of the organic solvent used is preferably 10 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the raw material monomer for the styrene-based resin segment.
[0041] The composite resin is more preferably a resin in which a polyester resin segment and a styrene-based resin segment are chemically bonded via a bireactive monomer that can react with both the raw material monomer of the polyester resin segment and the raw material monomer of the styrene-based resin segment.
[0042] The bireactive monomer is preferably a compound having at least one functional group selected from the group consisting of hydroxyl, carboxyl, epoxy, primary amino, and secondary amino groups, preferably a hydroxyl and / or carboxyl group, more preferably a carboxyl group, and an ethylenically unsaturated bond in the molecule, more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, fumaric acid, maleic acid, and maleic anhydride, and even more preferably at least one selected from the group consisting of acrylic acid, methacrylic acid, and fumaric acid from the viewpoint of the reactivity of polycondensation reactions and addition polymerization reactions. However, when used together with a polymerization inhibitor, a polycarboxylic acid compound having an ethylenically unsaturated bond, such as fumaric acid, functions as a raw material monomer for the polyester resin segment. In this case, fumaric acid, etc., is not a bireactive monomer but a raw material monomer for the polyester resin segment.
[0043] The amount of the bireactive monomer used is preferably 1 mol or more, more preferably 2 mol or more, relative to 100 mol of the total alcohol components of the polyester resin segment, from the viewpoint of increasing the dispersibility of the styrene resin segment and the polyester resin segment and improving the durability of the toner, and from the viewpoint of low-temperature fixability, it is preferably 30 mol or less, more preferably 20 mol or less, and even more preferably 10 mol or less. The amount of the bireactive monomer used is preferably 1 part by mass or more, more preferably 2 parts by mass or more, relative to 100 parts by mass of the raw material monomers for the styrene resin segment, from the viewpoint of improving the dispersibility of the styrene resin segment and the polyester resin segment and improving the durability of the toner, and is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, from the viewpoint of low-temperature fixability. Here, the total amount of the raw material monomers for the styrene resin segment includes the polymerization initiator.
[0044] Specifically, the composite resin is preferably produced by the following method: When a bireactive monomer is used, the bireactive monomer is preferably used in an addition polymerization reaction together with a raw material monomer of a styrene-based resin segment, from the viewpoint of improving the charge stability and low-temperature fixability of the toner.
[0045] The composite resin can be produced, for example, by a method including step (X) of polycondensation reaction of raw material monomers for the polyester resin segment and step (Y) of addition polymerization reaction of raw material monomers for the styrene resin segment. (i) Step (Y) may be performed after step (X), (ii) Step (X) may be performed after step (Y), or (iii) Step (X) and Step (Y) may be performed simultaneously.
[0046] In the method (i), after the step (Y), the reaction temperature may be increased again, and if necessary, a raw material monomer of a trivalent or higher polyester resin segment that serves as a crosslinking agent may be added to the reaction system, thereby further promoting the polycondensation reaction of the step (X) or the reaction with the bireactive monomer. Alternatively, a prepolymerized polyester resin may be used instead of the polycondensation reaction in step (X). When steps (X) and (Y) are carried out in parallel, a mixture containing raw material monomers for the styrene resin segment may be added dropwise to a mixture containing raw material monomers for the polyester resin segment to cause the reaction.
[0047] The above methods (i) to (iii) are preferably carried out in the same container.
[0048] The mass ratio of the polyester resin segment to the styrene-based resin segment in the composite resin is preferably 98 / 2 or less, more preferably 95 / 5 or less, and even more preferably 90 / 10 or less, from the viewpoint of charging stability, and is preferably 60 / 40 or more, more preferably 70 / 30 or more, and even more preferably 75 / 25 or more, from the viewpoint of low-temperature fixability. Here, the mass of the polyester resin segment is the amount of raw material monomers used for the polyester resin segment minus the amount of reaction water (calculated value) dehydrated by the polycondensation reaction, and the amount of the bireactive monomer is included in the amount of raw material monomers for the polyester resin segment. Furthermore, the mass of the styrene-based resin segment is the total amount of raw material monomers for the styrene-based resin segment and polymerization initiator.
[0049] The amount of the monomer having an unsaturated bond in the polymer having an unsaturated bond (A) is preferably 0.01 mmol or more, more preferably 0.03 mmol or more, and even more preferably 0.05 mmol or more, per gram of the polymer having an unsaturated bond, from the viewpoint of hot offset resistance, and is preferably 3 mmol or less, more preferably 2 mmol or less, and even more preferably 1.5 mmol or less, from the viewpoint of low-temperature fixability.
[0050] The softening point of the polymer (A) having an unsaturated bond is preferably 80°C or higher, more preferably 90°C or higher, and even more preferably 95°C or higher from the viewpoint of storage stability, and is preferably 160°C or lower, more preferably 150°C or lower, and even more preferably 140°C or lower from the viewpoint of low-temperature fixability.
[0051] The glass transition temperature of the polymer (A) having an unsaturated bond is preferably 40°C or higher, more preferably 50°C or higher, from the viewpoint of storage stability, and is preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 65°C or lower, from the viewpoint of low-temperature fixability.
[0052] The acid value of the polymer (A) having an unsaturated bond is preferably 2 mgKOH / g or more, more preferably 5 mgKOH / g or more, from the viewpoint of low-temperature fixability, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, from the viewpoint of moisture absorption.
[0053] The weight average molecular weight of the polymer (A) having an unsaturated bond is preferably 1,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more from the viewpoint of storage stability, and is preferably 1,000,000 or less, more preferably 750,000 or less, and even more preferably 500,000 or less from the viewpoint of low-temperature fixability.
[0054] From the same viewpoint, the number average molecular weight of the polymer (A) having an unsaturated bond is preferably 500 or more, more preferably 1,500 or more, even more preferably 2,000 or more, and preferably 10,000 or less, more preferably 7,500 or less, even more preferably 5,000 or less.
[0055] The physical properties of the polymer (A) having an unsaturated bond are measured in the same manner as for the binder resin.
[0056] The addition polymerization resin segment is preferably a styrene-based resin segment, and the addition polymerizable monomer preferably includes a raw material monomer for a styrene-based resin, such as styrene, α-methylstyrene, vinyltoluene, or other styrene derivatives (hereinafter, styrene and styrene derivatives are collectively referred to as "styrene compounds").
[0057] The content of the styrene compound, preferably styrene, in the addition polymerizable monomer is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, from the viewpoint of storage stability under high humidity conditions, and is preferably 95% by mass or less, more preferably 93% by mass or less, and even more preferably 90% by mass or less, from the viewpoint of low-temperature fixability.
[0058] The addition-polymerizable monomer may also contain a (meth)acrylic acid alkyl ester having an alkyl group with 7 or more carbon atoms. Examples of the (meth)acrylic acid alkyl ester include 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, and (iso)stearyl (meth)acrylate. It is preferable to use one or more of these. In this specification, "(iso)" means both the presence and absence of this group, and indicates normal when this group is not present. Furthermore, "(meth)acrylic acid" refers to acrylic acid, methacrylic acid, or both.
[0059] From the viewpoint of improving the low-temperature fixability of the toner, the number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester as an addition-polymerizable monomer is preferably 7 or more, more preferably 8 or more, and preferably 12 or less, more preferably 10 or less. The number of carbon atoms in the alkyl ester refers to the number of carbon atoms derived from the alcohol component constituting the ester.
[0060] The addition-polymerizable monomer may include monomers other than styrene compounds and (meth)acrylic acid alkyl esters, for example, ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; ethylenic monocarboxylic acid esters such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as methyl vinyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone.
[0061] The bireactive monomer is a monomer that can react with both polycondensation monomers and addition polymerizable monomers. The bireactive monomer is preferably a compound having, in the molecule, at least one functional group selected from the group consisting of hydroxyl groups, carboxyl groups, epoxy groups, primary amino groups, and secondary amino groups, preferably a hydroxyl group and / or a carboxyl group, more preferably a carboxyl group, and an ethylenically unsaturated bond. At least one selected from the group consisting of acrylic acid, methacrylic acid, fumaric acid, maleic acid, and maleic anhydride is more preferred. From the viewpoint of the reactivity of polycondensation reactions and addition polymerization reactions, at least one selected from the group consisting of acrylic acid, methacrylic acid, and fumaric acid is even more preferred. However, when used together with a polymerization inhibitor, a polycarboxylic acid compound having an ethylenically unsaturated bond, such as fumaric acid, functions as a raw material monomer for polyester resin segments. In this case, fumaric acid, etc., is not a bireactive monomer but a raw material monomer for polyester resin segments.
[0062] The amount of the bireactive monomer used is preferably 1 mol or more, more preferably 2 mol or more, relative to 100 mol of the total alcohol components of the polyester resin segment, from the viewpoint of increasing the dispersibility of the styrene resin segment and the polyester resin segment and improving the durability of the toner, and from the viewpoint of low-temperature fixability, it is preferably 30 mol or less, more preferably 20 mol or less, and even more preferably 10 mol or less. The amount of the bireactive monomer used is preferably 1 part by mass or more, more preferably 2 parts by mass or more, relative to 100 parts by mass of the raw material monomers for the styrene resin segment, from the viewpoint of improving the dispersibility of the styrene resin segment and the polyester resin segment and improving the durability of the toner, and is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, from the viewpoint of low-temperature fixability. Here, the total amount of the raw material monomers for the styrene resin segment includes the polymerization initiator.
[0063] The polycondensation resin segment is preferably a polyester resin segment, and the polycondensation monomer contains an alcohol component and a carboxylic acid component.
[0064] The alcohol component preferably contains an alkylene oxide adduct of bisphenol A. The alkylene oxide adduct of bisphenol A is preferably a compound represented by the above formula (I).
[0065] From the viewpoint of low-temperature fixability, the content of the alkylene oxide adduct of bisphenol A in the alcohol component is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, even more preferably 95 mol% or more, and even more preferably 100 mol%.
[0066] Examples of other alcohol components include aliphatic diols, bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, tri- or higher hydric alcohols such as trimethylolpropane, and the like.
[0067] The carboxylic acid component preferably contains an aromatic dicarboxylic acid compound.
[0068] Examples of aromatic dicarboxylic acid compounds include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0069] From the viewpoint of low-temperature fixability, the content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 40 mol % or more, more preferably 50 mol % or more, and 100 mol % or less, preferably 90 mol % or less.
[0070] Examples of the carboxylic acid component other than the aromatic dicarboxylic acid compound include an aliphatic dicarboxylic acid compound and a trivalent or higher carboxylic acid compound.
[0071] Examples of the aliphatic dicarboxylic acid compound include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid which may be substituted with a hydrocarbon group having 1 to 20 carbon atoms, adipic acid, and the like; anhydrides of these acids; and alkyl esters in which the alkyl group has 1 to 3 carbon atoms.
[0072] Examples of the trivalent or higher carboxylic acid compound include trimellitic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0073] The equivalent ratio of the carboxyl groups of the carboxylic acid component to the hydroxyl groups of the alcohol component (COOH groups / OH groups) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.75 or more, and is preferably 1.2 or less, more preferably 1.15 or less.
[0074] The binder resin for toner in the present invention is produced by a method comprising: step A, in which an addition-polymerizable monomer and a bireactive monomer are addition-polymerized in the presence of a polymer (A) having an unsaturated bond; and step B, in which a polycondensable monomer containing a carboxylic acid component and an alcohol component is polycondensed; and the steps A and B are carried out in the same reaction vessel.
[0075] In the step A, the amount of the monomer having an unsaturated bond constituting the polymer (A) having an unsaturated bond is 5.0×10 relative to 1 g of the total amount of the addition polymerizable monomer, the bireactive monomer, and the polycondensation monomer, from the viewpoint of hot offset resistance. -5 mmol or more, preferably 1.0 × 10 -4 mmol or more, preferably 3.0 × 10 -4 mmol or more, more preferably 5.0 × 10 -4 mmol or more, and from the viewpoint of low-temperature fixability, -2 mmol or less, preferably 1.9 × 10 -2 mmol or less, preferably 1.8 × 10 -2 mmol or less, more preferably 1.75 × 10-2 It is less than mmol.
[0076] The amount of the polymer (A) having an unsaturated bond used in step A is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.08 parts by mass or more, and is preferably 2.8 parts by mass or less, more preferably 2.6 parts by mass or less, even more preferably 2.4 parts by mass or less, relative to 100 parts by mass of the total amount of the polycondensation resin segment and the addition polymerization resin segment. The amount of the polycondensation resin segment is the theoretical yield calculated by subtracting the amount of reaction water from the total amount of polycondensation monomers, and the amount of the addition polymerization resin segment is the total amount of the addition polymerizable monomers and the polymerization initiator.
[0077] In step A, the addition polymerization reaction can be carried out by a conventional method in the presence of a polymerization initiator such as dibutyl peroxide or dicumyl peroxide, a chain transfer agent, a crosslinking agent, or the like, in the presence of an organic solvent or in the absence of a solvent. The temperature conditions are preferably 110°C or higher, more preferably 140°C or higher, and preferably 200°C or lower, more preferably 170°C or lower.
[0078] When an organic solvent is used in the addition polymerization reaction, xylene, toluene, methyl ethyl ketone, acetone, etc. can be used. The amount of the organic solvent used is preferably 10 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the raw material monomer for the styrene-based resin segment.
[0079] In step B, for example, when an alcohol component and a carboxylic acid component are used as polycondensable monomers, the polycondensation reaction can be carried out in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and further, if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature of preferably 130°C or higher, more preferably 170°C or higher, and preferably 250°C or lower, more preferably 240°C or lower.
[0080] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanolamine. The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, per 100 parts by mass of the alcohol component and the carboxylic acid component combined. Examples of the esterification promoter include gallic acid. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, per 100 parts by mass of the alcohol component and the carboxylic acid component combined. Examples of the polymerization inhibitor include t-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0081] The order of step A and step B is not particularly limited as long as step A is carried out in the presence of polymer (A) having an unsaturated bond. (i) step B may be carried out after step A, (ii) step A may be carried out after step B, or (iii) step A and step B may be carried out simultaneously. In the present invention, however, from the viewpoint of the reactivity of polymer (A) and the addition-polymerizable monomer, method (i) in which step B is carried out after step A is preferred.
[0082] In the method (i), step A may be carried out in the presence of a polycondensable monomer and polymer (A), and in this case, it is preferable to appropriately add an esterification catalyst, an esterification promoter, etc. to the reaction system after step A and carry out step B under temperature conditions suitable for the polycondensation reaction. In addition, in the method (ii), step B may be carried out in the presence of polymer (A), and then step A may be carried out subsequently.
[0083] The mass ratio of the polycondensation resin segment to the addition polymerization resin segment in the binder resin is preferably 98 / 2 or less, more preferably 95 / 5 or less, and even more preferably 90 / 10 or less from the viewpoint of charging stability, and is preferably 60 / 40 or more, more preferably 70 / 30 or more, and even more preferably 75 / 25 or more from the viewpoint of low-temperature fixability. Here, the mass of the polycondensation resin segment is the total amount of the polycondensation monomer and bireactive monomer used, minus the amount of reaction water (calculated value) dehydrated by the polycondensation reaction. Furthermore, the mass of the addition polymerization resin segment is the total amount of the addition polymerizable monomer and polymerization initiator.
[0084] The softening point of the binder resin is preferably 80° C. or higher, more preferably 90° C. or higher, from the viewpoint of storage stability, and is preferably 150° C. or lower, more preferably 130° C. or lower, from the viewpoint of low-temperature fixability.
[0085] The glass transition temperature of the binder resin is preferably 50° C. or higher, more preferably 53° C. or higher, from the viewpoint of storage stability, and is preferably 70° C. or lower, more preferably 65° C. or lower, from the viewpoint of low-temperature fixability.
[0086] The acid value of the binder resin is preferably 2 mgKOH / g or more, more preferably 5 mgKOH / g or more, from the viewpoint of low-temperature fixability, and is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less, from the viewpoint of moisture absorption.
[0087] The weight average molecular weight of the binder resin is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more from the viewpoint of storage stability, and is preferably 200,000 or less, more preferably 150,000 or less, and even more preferably 100,000 or less from the viewpoint of low-temperature fixability.
[0088] Similarly, the number average molecular weight of the binder resin is preferably 1,000 or more, more preferably 1,500 or more, and even more preferably 2,000 or more, and from the viewpoint of low-temperature fixability, it is preferably 10,000 or less, more preferably 5,000 or less, and even more preferably 3,000 or less.
[0089] A toner for developing electrostatic images is obtained using the binder resin obtained by the method of the present invention. The content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, and preferably less than 100% by mass, more preferably 98% by mass or less, and even more preferably 95% by mass or less. The binder resin may contain resins other than the binder resin obtained by the method of the present invention, and the content of such binder resins is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more of the total amount of binder resins.
[0090] The toner may contain additives such as a colorant, a release agent, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver in addition to the binder resin.
[0091] As the colorant, dyes, pigments, magnetic materials, etc. used as toner colorants can be used. Examples include carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, pigment yellow, disazo yellow, etc. In the present invention, the toner may be either a black toner or a color toner.
[0092] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0093] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, polypropylene-polyethylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts, and these may be used alone or in combination of two or more.
[0094] The melting point of the release agent is preferably 60°C or higher, more preferably 70°C or higher, from the viewpoint of toner transferability, and is preferably 160°C or lower, more preferably 140°C or lower, even more preferably 120°C or lower, and even more preferably 110°C or lower, from the viewpoint of low-temperature fixability.
[0095] The content of the release agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 1.5 parts by mass or more, relative to 100 parts by mass of the binder resin, from the viewpoints of the low-temperature fixability and offset resistance of the toner and the dispersibility in the binder resin, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less.
[0096] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.
[0097] Examples of positively chargeable charge control agents include nigrosine dyes such as "Nigrosine Base EX," "Oil Black BS," "Oil Black SO," "Bontron N-01," "Bontron N-04," "Bontron N-07," "Bontron N-09," and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of suitable resins include polyamine resins such as "AFP-B" (manufactured by Orient Chemical Industries Co., Ltd.); imidazole derivatives such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Chemical Industry Co., Ltd.); and styrene-acrylic resins such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Chemical Industries Co., Ltd.).
[0098] Examples of negatively chargeable charge control agents include metal-containing azo dyes such as "Balifast Black 3804," "Bontron S-31," "Bontron S-32," "Bontron S-34," and "Bontron S-36" (all manufactured by Orient Chemical Industries, Ltd.), "Eisenspiron Black TRH," and "T-77" (manufactured by Hodogaya Chemical Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81," "Bontron E-84," "Bontron E-88," and "Bontron E-304" (all manufactured by Orient Chemical Industries, Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (manufactured by Clariant), nitroimidazole derivatives, etc.; organometallic compounds, etc.
[0099] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0100] The toner can be produced by any of the conventionally known methods such as a melt-kneading method, an emulsion phase inversion method, and a polymerization method. However, in the present invention, from the viewpoint of low-temperature fixability, it is preferable to produce the toner by a method including a step (I) of dispersing the toner binder resin obtained by the method of the present invention in an aqueous medium to obtain resin particles, and a step (II) of aggregating and fusing the resin particles to obtain toner particles.
[0101] In step (I), methods for obtaining resin particles include a method of adding a resin component or the like to an aqueous medium and performing a dispersion treatment using a disperser or the like, a method of gradually adding an aqueous medium to a melt or an organic solvent solution of the resin component or the like to cause phase inversion emulsification (phase inversion emulsification), etc. Among these, the phase inversion emulsification method is preferred from the viewpoint of improving the low-temperature fixability and durability of the toner.
[0102] Examples of the phase inversion emulsification method include method (A) in which a resin component, etc. is dissolved in an organic solvent to obtain an organic solvent solution of the resin component, etc., and an aqueous medium is added to the obtained solution to perform phase inversion emulsification, and method (B) in which an aqueous medium is added to a resin mixture obtained by melting and mixing the resin component, etc. Method (A) is preferred from the viewpoint of obtaining a homogeneous aqueous dispersion of core resin particles.
[0103] The organic solvent used for phase inversion emulsification is not particularly limited as long as it dissolves the resin, and examples thereof include methyl ethyl ketone.
[0104] The amount of the organic solvent used is preferably 30 parts by mass or more and 1000 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0105] The amount of the aqueous medium used is preferably 100 to 3,000 parts by mass relative to 100 parts by mass of the organic solvent. The aqueous medium used in step (I) may contain an alcohol solvent having 1 to 3 carbon atoms, such as ethanol, but preferably contains 50% by mass or more of water, more preferably 70% by mass or more, even more preferably 90% by mass or more, and even more preferably 99% by mass or more.
[0106] When stirring the mixture, a commonly used mixing and stirring device such as an anchor blade can be used.
[0107] In the phase inversion emulsification method, it is preferable to treat the resin with a neutralizing agent. Examples of the neutralizing agent include alkali metals such as lithium hydroxide, sodium hydroxide, and potassium hydroxide; and organic bases such as ammonia, trimethylamine, ethylamine, diethylamine, triethylamine, triethanolamine, and tributylamine. The amount of neutralizing agent added is preferably an amount that results in a degree of neutralization of about 50 to 100% based on the acid value of the polyester after the neutralization reaction.
[0108] A surfactant or the like may be used as a dispersant for the purpose of lowering the melt viscosity and melting point of the binder resin and improving the dispersibility of the resulting resin particles.
[0109] The solid content of the dispersion of resin particles containing the binder resin obtained in step (I) is preferably 5% by mass or more, more preferably 10% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, from the viewpoints of dispersion stability and handleability in the aggregation step. The solid content includes non-volatile components such as resins and surfactants.
[0110] From the viewpoint of uniform aggregation in the subsequent step, the average particle size of the resin particles is preferably 0.05 μm or more, more preferably 0.10 μm or more, even more preferably 0.15 μm or more, and is preferably 0.80 μm or less, more preferably 0.40 μm or less, even more preferably 0.30 μm or less. In the present invention, the average particle size of the resin particles is defined as the volume median particle size (D 50 ) and can be measured using a laser diffraction particle size analyzer, etc.
[0111] Subsequently, the resin particles obtained in step (I) are aggregated and fused (step (II)).
[0112] In step (II), aggregation is performed by, for example, adding an aggregating agent to a mixed dispersion containing resin particles at a temperature of 0° C. to 40° C., and aggregating the resin particles in an aqueous medium to obtain aggregated particles. Furthermore, from the viewpoint of promoting aggregation, it is preferable to increase the temperature of the dispersion after adding the aggregating agent.
[0113] The temperature maintained during aggregation is preferably 45°C or higher, more preferably 50°C or higher, and preferably 80°C or lower, more preferably 70°C or lower, and even more preferably 65°C or lower.
[0114] In addition, additives such as colorants, release agents, and charge control agents may be mixed in advance with the binder resin when preparing the resin particles, or each additive may be separately mixed with an appropriate resin, surfactant, etc., and dispersed in a dispersion medium such as water to prepare a dispersion, which may then be mixed with the resin particles and subjected to the aggregation step. The resin mixed with the additives may be the same as or different from the binder resin.
[0115] As the flocculant, for organic systems, quaternary salt cationic surfactants, polyethyleneimine, etc. are used, and for inorganic systems, inorganic metal salts, inorganic ammonium salts, divalent or higher metal complexes, etc. are used. Examples of inorganic metal salts include metal salts such as sodium sulfate, sodium chloride, calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate, as well as inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. Examples of inorganic ammonium salts include ammonium sulfate, ammonium chloride, and ammonium nitrate.
[0116] From the viewpoint of controlling aggregation and obtaining a desired particle size, the amount of the aggregating agent used is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 20 parts by mass or more, relative to 100 parts by mass of the binder resin, and is preferably 60 parts by mass or less, and more preferably 50 parts by mass or less.
[0117] Subsequently, the aggregated particles containing at least the binder resin obtained in the aggregation step are heated and fused to obtain toner particles (fusion step).
[0118] When the fused particles have grown to a particle size appropriate for toner, the aggregation may be stopped by adding an aggregation stopper or the like.
[0119] The temperature in the system during the fusion step is, from the viewpoints of the target toner particle size, particle size distribution, shape control, and particle fusion properties, preferably at least 2°C higher, more preferably at least 4°C higher, and even more preferably at least 6°C higher than the maximum glass transition temperature of the binder resin, and is preferably not higher than 30°C higher, more preferably not higher than 20°C higher than the maximum glass transition temperature of the binder resin. Furthermore, the stirring speed is preferably a speed at which aggregated particles do not settle. In the present invention, when two or more resins are used as binder resins, the glass transition temperature of the resin with the highest glass transition temperature is used as the reference.
[0120] The fused particles obtained in step (II) can be subjected to a solid-liquid separation step such as filtration, a washing step, and a drying step as appropriate to obtain toner particles.
[0121] Toner preferably contains an external additive in order to improve transferability. Examples of external additives include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as resin particles such as melamine-based resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of these may be used in combination. Among these, silica is preferred, and from the viewpoint of toner transferability, hydrophobic silica that has been subjected to a hydrophobic treatment is more preferred.
[0122] Examples of hydrophobic treatment agents for hydrophobizing the surfaces of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), dimethylsiloxane, silicone oil, octyltriethoxysilane (OTES), and methyltriethoxysilane.
[0123] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle diameter of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.
[0124] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles before treatment with the external additive, and is preferably 5 parts by mass or less, and more preferably 4 parts by mass or less.
[0125] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50) means the particle size at which the cumulative volume frequency calculated by volume fraction is 50% starting from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is taken as the volume median particle size of the toner.
[0126] The toner of the present invention can be used as a toner for one-component development as it is, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively. [Example]
[0127] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.
[0128] [Softening point of resin] Using a flow tester "CFT-500EX" (Shimadzu Corporation), 1 g of sample is heated at a temperature increase rate of 6°C / min, while a load of 1.96 MPa is applied by the plunger, and the sample is extruded from a nozzle 1 mm in diameter and 1 mm in length. The plunger depression distance of the flow tester is plotted against the temperature, and the temperature at which half of the sample flows out is taken as the softening point.
[0129] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (TA Instruments Japan), weigh 0.01-0.02 g of sample into an aluminum pan, heat from room temperature (20°C) to 200°C at a rate of 10°C / min, and then cool from that temperature to 0°C at a rate of 10°C / min. Next, heat the sample at a rate of 10°C / min, and measure the endothermic peak. The glass transition temperature is the temperature at the intersection of an extension of the baseline below the maximum endothermic peak temperature and a tangent line showing the maximum slope from the rising part of the peak to the peak.
[0130] [Acid value of resin] Measurement is performed based on the method of JIS K0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K0070:1992 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)).
[0131] [Number average molecular weight and weight average molecular weight of resin] The number average molecular weight and weight average molecular weight are determined by gel permeation chromatography (GPC) according to the following method. (1) Preparation of sample solution The sample is dissolved in tetrahydrofuran at 40°C to a concentration of 0.5 g / 100 mL. Next, this solution is filtered using a PTFE-type membrane filter "DISMIC-25JP" (manufactured by Toyo Roshi Kaisha, Ltd.) with a pore size of 0.20 μm to remove insoluble components, and the resulting solution is used as the sample solution. (2) Molecular weight measurement The following measurement equipment and analytical column are used, and tetrahydrofuran is used as the eluent at a flow rate of 1 mL per minute. The column is stabilized in a thermostatic bath at 40°C. 100 μL of sample solution is injected into the column and measurement is performed. The molecular weight of the sample is calculated based on a calibration curve prepared in advance. The calibration curve used here is a series of monodisperse polystyrenes (A-500 (5.0 × 10) manufactured by Tosoh Corporation) 2 ), A-1000(1.01×10 3 ), A-2500(2.63×10 3 ), A-5000(5.97×10 3 ), F-1(1.02×10 4 ), F-2(1.81×10 4 ), F-4(3.97×10 4 ), F-10(9.64×10 4 ), F-20(1.90×10 5 ), F-40(4.27×10 5 ), F-80(7.06×10 5 ), F-128(1.09×10 6 )) was used as a standard sample. The molecular weight is indicated in parentheses. Measuring device: HLC-8220GPC (manufactured by Tosoh Corporation) Analytical column: TSKgel GMH XL +TSKgel G3000H XL (Manufactured by Tosoh Corporation)
[0132] [Melting point of release agent] Using a differential scanning calorimeter "DSC Q20" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C at a heating rate of 10°C / min, and cooled from that temperature to -10°C at a cooling rate of 5°C / min. Next, the sample is heated to 180°C at a heating rate of 10°C / min and measured. The maximum endothermic peak temperature observed in the melting endothermic curve obtained is taken as the melting point of the release agent.
[0133] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average values of major and minor axes) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these values by number.
[0134] [Volume Median Particle Size and CV Value of Resin Particles, Colorant Particles, and Release Agent Particles] (1) Measuring device: Laser diffraction particle size measuring instrument "LA-920" (manufactured by Horiba, Ltd.) (2) Measurement conditions: Put the sample dispersion into a measurement cell, add distilled water, and measure the volume median particle size (D) at a concentration where the absorbance is in the appropriate range. 50 ) and volume average particle diameter (Dv). The coefficient of variation CV value is calculated according to the following formula. CV value (%) = (standard deviation of particle size distribution / volume average particle size (Dv)) x 100
[0135] [Solid Content Concentration of Resin Particle Dispersion, Colorant Particle Dispersion, and Release Agent Particle Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), measure the moisture content (mass%) of 5 g of the sample at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, moisture content fluctuation range 0.05%). Calculate the solid content concentration according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0136] [Volume median particle size of aggregated particles and toner particles (D 50 ) and CV value] Measuring instrument: Coulter Multisizer II (manufactured by Beckman Coulter, Inc.) Aperture diameter: 100 μm Analysis software: Coulter Multisizer AccuComp version 1.19 (Beckman Coulter, Inc.) Electrolyte: Isoton II (Beckman Coulter, Inc.) Dispersion liquid: Emulgen 109P (Kao Corporation, polyoxyethylene lauryl ether, HLB (Griffin): 13.6) dissolved in electrolyte to adjust to 5% by mass (for aggregated particles, the dispersion liquid was used as is) Dispersion conditions: 10 mg of the measurement sample was added to 5 mL of the dispersion, and the mixture was dispersed for 1 minute using an ultrasonic disperser (machine name: US-1 manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of the electrolyte solution was added, and the mixture was further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte solution so that the particle size of 30,000 particles could be measured in 20 seconds. 30,000 particles were measured, and the volume median particle size (D 50 The coefficient of variation (CV) is calculated from the particle size distribution obtained according to the following formula: CV value (%) = (standard deviation of particle size distribution / volume average particle size (Dv)) x 100
[0137] [Circularity of fused particles] The circularity of the fused particles is measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: A dispersion of fused particles is prepared by diluting it with deionized water so that the solid content concentration is 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0138] Preparation Example 1 of Polymer Having Unsaturated Bond The alcohol components and terephthalic acid shown in Table 1 were placed in a 10 L four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple. The temperature was raised to 160°C under a nitrogen atmosphere, and a monomer mixture consisting of raw material monomers for the styrene resin, a bireactive monomer, and a polymerization initiator was added dropwise over 1 hour. After aging at 160°C for 30 minutes, the temperature was raised to 200°C. After reaching 200°C, unreacted monomers were removed under a reduced pressure of 8 kPa for 1 hour. After cooling to 150°C, an esterification catalyst and an esterification cocatalyst were added, and the temperature was raised to 235°C and an esterification reaction was carried out for 8 hours. After the reaction was continued under a reduced pressure of 8 kPa for 1 hour, the temperature was lowered to 160°C, fumaric acid and a polymerization inhibitor were added, and the temperature was raised again to 190°C. After reaching 190°C and maintaining the temperature for 30 minutes, the temperature was raised to 210°C at a rate of 10°C / h and maintained for 2 hours. Thereafter, the mixture was reacted at 66.7 kPa while maintaining the temperature at 210° C. until the softening point shown in Table 1 was reached, thereby obtaining a composite resin having an unsaturated bond (resin A1). The physical properties of the obtained resin are shown in Table 1.
[0139] Preparation Example 2 of Polymer Having Unsaturated Bond The alcohol components and terephthalic acid shown in Table 1 were placed in a 10 L four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple. The flask was heated to 160°C under a nitrogen atmosphere, and a monomer mixture consisting of raw material monomers for the styrene resin, a bireactive monomer, and a polymerization initiator was added dropwise over 1 hour. The mixture was then aged at 160°C for 30 minutes, then heated to 200°C. After reaching 200°C, unreacted monomers were removed under a reduced pressure of 8 kPa for 1 hour. After cooling to 150°C, an esterification catalyst and an esterification cocatalyst were added, and the mixture was heated to 235°C and esterification reaction was carried out for 8 hours. After the reaction was continued for 1 hour under a reduced pressure of 8 kPa, the mixture was cooled to 160°C, and fumaric acid, trimellitic anhydride, and a polymerization inhibitor were added. The mixture was then heated again to 190°C. After reaching 190°C, the mixture was held for 30 minutes, then heated to 210°C at a rate of 10°C / h, and held for 2 hours. The mixture was then allowed to react at 66.7 kPa while maintaining the temperature at 210°C until the softening point shown in Table 1 was reached, yielding composite resins having unsaturated bonds (Resins A2 and A3). The physical properties of the resulting resins are shown in Table 1.
[0140] Preparation Example 3 of Polymer Having Unsaturated Bond The alcohol component, terephthalic acid, esterification catalyst, and esterification cocatalyst shown in Table 1 were placed in a 10 L four-neck flask equipped with a nitrogen inlet tube, stirrer, and thermocouple. The mixture was heated to 235°C under a nitrogen atmosphere and subjected to an esterification reaction for 8 hours. After the reaction was continued for 1 hour under a reduced pressure of 8 kPa, the temperature was lowered to 160°C, and fumaric acid or maleic acid and a polymerization inhibitor were added. The temperature was then raised again to 190°C. After reaching 190°C and holding for 30 minutes, the temperature was raised to 210°C at a rate of 10°C / h and held for 2 hours. The reaction was continued at 210°C under 66.7 kPa until the softening point shown in Table 1 was reached, yielding polyester resins with unsaturated bonds (Resins A4 and A5). The physical properties of the resulting resins are shown in Table 1.
[0141] [Table 1]
[0142] Examples A1, A3 to A9 and Comparative Examples A2 and A3 The polycondensable monomers other than succinic acid or fumaric acid and the polymer (A) having an unsaturated bond shown in Tables 2 and 3 were placed in a 10-L four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple. The flask was heated to 160°C under a nitrogen atmosphere, and a monomer mixture consisting of an addition-polymerizable monomer, a bireactive monomer, and a polymerization initiator was added dropwise over 1 hour. After aging at 160°C for 30 minutes, the mixture was heated to 200°C and maintained at a reduced pressure of 8 kPa for 1 hour. After cooling to 150°C, an esterification catalyst and an esterification cocatalyst were added, and the mixture was heated to 235°C and esterification reaction was carried out for 8 hours. After the reaction was continued for 1 hour under a reduced pressure of 8 kPa, the mixture was cooled to 160°C, succinic acid or fumaric acid was added, and the mixture was heated again to 190°C. After reaching 190°C, the mixture was held for 30 minutes, and then reacted at 40 kPa until the softening point shown in Tables 2 and 3 was reached, thereby obtaining composite resins (resins B2, B4 to B12). The physical properties of the obtained resins are shown in Tables 2 and 3.
[0143] Example A2 The polycondensable monomers other than succinic acid, Resin A1, esterification catalyst, and esterification cocatalyst shown in Table 2 were placed in a 10 L four-neck flask equipped with a nitrogen inlet tube, stirrer, and thermocouple. The mixture was heated to 235°C under a nitrogen atmosphere and subjected to an esterification reaction for 8 hours. After 1 hour of reaction under a reduced pressure of 8 kPa, the temperature was lowered to 160°C, and a monomer mixture consisting of an addition-polymerizable monomer, a bireactive monomer, and a polymerization initiator was added dropwise over 1 hour. After aging at 160°C for 30 minutes, the mixture was heated to 200°C and maintained at a reduced pressure of 8 kPa for 1 hour. After lowering the temperature to 160°C, succinic acid was added and the mixture was heated again to 190°C. After maintaining the temperature at 190°C for 30 minutes, the mixture was reacted at 40 kPa until the softening point shown in Table 2 was reached, yielding a composite resin (Resin B3). The physical properties of the resulting resin are shown in Table 2.
[0144] Comparative Example A1 The polycondensable monomers other than succinic acid and Resin A1 shown in Table 2 were placed in a 10 L four-neck flask equipped with a nitrogen inlet tube, stirrer, and thermocouple. The temperature was raised to 160°C under a nitrogen atmosphere, and a monomer mixture consisting of an addition-polymerizable monomer, a bireactive monomer, and a polymerization initiator was added dropwise over 1 hour. After aging at 160°C for 30 minutes, the temperature was raised to 200°C. After reaching 200°C, the mixture was maintained under a reduced pressure of 8 kPa for 1 hour. After cooling to 150°C, an esterification catalyst and esterification co-catalyst were added, and the mixture was heated to 235°C and esterification reaction was carried out for 8 hours. After reaction under a reduced pressure of 8 kPa for 1 hour, the mixture was cooled to 160°C, succinic acid was added, and the mixture was heated again to 190°C. After reaching 190°C, the mixture was maintained for 30 minutes and then reacted at 40 kPa until the softening point listed in Table 2 was reached, yielding a composite resin (Resin B1). The physical properties of the resulting resin are shown in Table 2.
[0145] Comparative examples A4, A5 The polycondensable monomers other than succinic acid, Resin A4 (Comparative Example A5 only), esterification catalyst, and esterification co-catalyst shown in Table 3 were placed in a 10 L four-neck flask equipped with a nitrogen inlet tube, a stirrer, and a thermocouple. The mixture was heated to 235°C under a nitrogen atmosphere and subjected to an esterification reaction for 8 hours. After the reaction was continued for 1 hour under a reduced pressure of 8 kPa, the temperature was lowered to 160°C, succinic acid was added, and the temperature was raised again to 190°C. After reaching 190°C, the mixture was held for 30 minutes and then reacted at 40 kPa until the softening point shown in Table 3 was reached, yielding polyester resins (Resins B13 and B14). The physical properties of the resulting resins are shown in Table 3.
[0146] [Table 2]
[0147] [Table 3]
[0148] Hereinafter, examples of toner production using the obtained resins will be shown, but since resin B7 of Comparative Example A3 was obtained in a gelled state, it could not be used as a binder resin and was not used.
[0149] Manufacturing example of resin particle dispersion A 3-L vessel equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube was charged with 200 g of the resin shown in Table 4 and 200 g of methyl ethyl ketone, and the mixture was dissolved at 73°C for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution to achieve a neutralization degree of 60 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C and stirring at 200 r / min, 700 g of deionized water was added over 50 minutes to induce phase inversion emulsification. While maintaining the temperature at 73°C, the methyl ethyl ketone was distilled off under reduced pressure to obtain a dispersion. The dispersion was then cooled to 30°C with continued stirring, and deionized water was added to obtain a solids concentration of 20% by mass, yielding resin particle dispersions X1 to X13. The physical properties of the resin particles in the dispersions are shown in Table 4.
[0150] [Table 4]
[0151] Manufacturing example of resin for dispersing release agents The inside of a 10 L four-neck flask equipped with a nitrogen inlet tube, dehydration tube, stirrer, and thermocouple was replaced with nitrogen. The raw material monomers for the polyester resin segment other than succinic acid, the esterification catalyst, and the esterification co-catalyst shown in Table 5 were added. Under a nitrogen atmosphere, the reaction system was stirred and heated to 235°C. After maintaining this temperature for 5 hours, the pressure inside the flask was reduced and maintained at 8 kPa for 1 hour. The system was then returned to atmospheric pressure and cooled to 160°C. While maintaining this temperature, a mixture of raw material monomers for the styrene-based resin segment, a bireactive monomer, and a polymerization initiator was added dropwise to the reaction system over 1 hour. The reaction system was then maintained at 160°C for 30 minutes, after which it was heated to 200°C. The pressure inside the flask was further reduced and maintained at 8 kPa for 1 hour. The pressure was then returned to atmospheric pressure, cooled to 190°C, and succinic acid was added. The temperature was raised to 210°C at a rate of 10°C / h, and then the reaction was continued at 4 kPa until the desired softening point was reached, thereby obtaining Resin D1. Table 5 shows the physical properties of the obtained resin.
[0152] [Table 5]
[0153] Example of manufacturing a release agent particle dispersion 200 g of Resin D1 and 200 g of methyl ethyl ketone were placed in a 3 L vessel equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube and dissolved at 73°C for 2 hours. A 5% by mass aqueous solution of sodium hydroxide was added to the resulting solution to achieve a neutralization degree of 60 mol% relative to the acid value of Resin D1, and the mixture was stirred for 30 minutes. Next, while maintaining the temperature at 73°C and stirring at 280 r / min, 700 g of deionized water was added over 50 minutes to induce phase inversion emulsification. While maintaining the temperature at 73°C, the methyl ethyl ketone was distilled off under reduced pressure to obtain an aqueous dispersion. The aqueous dispersion was then cooled to 30°C while stirring at 280 r / min, and deionized water was added to obtain a solids concentration of 20% by mass to obtain Resin Particle Dispersion S1. The resin particles had a volume median particle diameter of 0.9 μm and a CV value of 23%.
[0154] To a 1 L beaker, 120 g of deionized water, 86 g of resin particle dispersion S1, and 40 g of the release agent shown in Table 6 were added, and the mixture was stirred while maintaining the temperature at 90 to 95°C to melt, yielding a molten mixture. The resulting molten mixture was dispersed for 20 minutes using an ultrasonic homogenizer "US-600T" (manufactured by Nippon Seiki Seisakusho Co., Ltd.) while maintaining the temperature at 90 to 95°C, and then cooled to room temperature (20°C). Deionized water was added to the resulting dispersion to adjust the solids concentration to 20 mass%, yielding release agent particle dispersions W1 and W2. Table 6 shows the physical properties of the release agent particles in the dispersions.
[0155] [Table 6]
[0156] Manufacturing example of colorant dispersion resin 16 g of methacrylic acid, 44 g of styrene, 30 g of styrene macromonomer "AS-6S" (manufactured by Toagosei Co., Ltd., number average molecular weight 6,000, solids concentration 50% by mass), and 25 g of methoxypolyethylene methacrylate "BLEMMER PME-200" (manufactured by NOF Corporation) were mixed to prepare 115 g of a monomer mixture with a total monomer amount of 100 g. The inside of a four-neck flask equipped with a nitrogen inlet tube, dropping funnel, stirrer, and thermocouple was purged with nitrogen, and 18 g of methyl ethyl ketone, 0.03 g of 2-mercaptoethanol, and 10% of the monomer mixture were added, and the temperature was raised to 75°C with stirring. While the reaction system was maintained at 75°C, a mixture of the remaining 90% of the monomer mixture, 0.27 g of 2-mercaptoethanol, 42 g of methyl ethyl ketone, and 3 g of 2,2'-azobis(2,4-dimethylvaleronitrile) "V-65" (Fujifilm Wako Pure Chemical Industries, Ltd.) was added dropwise to the reaction system over 3 hours using a dropping funnel. After the addition was completed, the reaction system was maintained at 75°C for 2 hours, and then a solution of 3 g of "V-65" dissolved in 5 g of methyl ethyl ketone was added. The mixture was then maintained at 75°C for 2 hours and then at 80°C for 2 hours. The methyl ethyl ketone was then distilled off under reduced pressure to obtain Resin E1. The weight-average molecular weight of the resulting resin was 50,000.
[0157] Example of manufacturing colorant particle dispersion A 5L vessel equipped with a stirrer equipped with a disperser blade, a reflux condenser, a dropping funnel, a thermometer, and a nitrogen inlet tube was charged with 75g of Resin E1 and 630g of methyl ethyl ketone, and the resin was dissolved at 20°C. To the resulting solution, 101g of 5% by mass aqueous sodium hydroxide (an amount sufficient to neutralize Resin E1 to 91 moles) was added, followed by 955g of deionized water. The mixture was stirred with a disperser blade at 2000 r / min for 10 minutes at 20°C. Next, 300g of Pigment Yellow 155 (Clariant Chemicals Co., Ltd., "Toner Yellow 3GP-CT", molecular weight 717) was added, and the mixture was stirred with a disperser blade at 6400 r / min for 2 hours at 20°C. The mixture was then passed through a 200-mesh filter and subjected to 15 passes at 150 MPa using a homogenizer "Microfluidizer M-110EH" (Microfluidics). The resulting dispersion was stirred under reduced pressure at 70°C to remove methyl ethyl ketone and some of the water. After cooling, the mixture was passed through a 200-mesh filter, and deionized water was added to adjust the solids concentration to 20% by mass, yielding colorant particle dispersion Z1. The colorant particles in the dispersion had a volume median particle size of 0.10 μm and a CV value of 28%.
[0158] Examples B1 to B9 Comparative Examples B1 to B4 500 g of the resin particle dispersion shown in Table 7, 49 g of release agent particle dispersion W1, 49 g of release agent particle dispersion W2, 63 g of colorant particle dispersion Z1, and 3.3 g of a 15% by mass aqueous solution of sodium dodecylbenzenesulfonate "Neopelex G-15" (Kao Corporation, anionic surfactant) were placed in a 3 L four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, and mixed at a temperature of 25° C. Next, while stirring the mixture, a solution prepared by dissolving 43 g of ammonium sulfate in 980 g of deionized water and adding a 4.8% by mass aqueous solution of potassium hydroxide to adjust the pH to 8.2 was added dropwise over 10 minutes at 25° C., and the temperature was then raised to 58° C. over 2 hours to measure the volume median particle diameter (D 50The temperature was maintained at 58°C until the circularity reached 5.0 µm, thereby obtaining a dispersion of aggregated particles. To the obtained dispersion of aggregated particles, 22 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (manufactured by Kao Corporation, anionic surfactant, effective concentration 27% by mass) and 1,100 g of deionized water were added. The temperature was then raised to 78°C over one hour, and the temperature was maintained at 78°C until the circularity reached 0.970, thereby obtaining a dispersion of fused particles in which the aggregated particles were fused together. The obtained dispersion of fused particles was cooled to 30°C, and the dispersion was subjected to suction filtration to separate the solid content, which was then washed with deionized water at 25°C and suction filtrated for 2 hours at 25°C. Thereafter, the solid content was vacuum dried at 33°C for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC Corporation) to obtain toner particles. 100 parts by mass of toner particles, 2.5 parts by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm), and 1.0 part by mass of hydrophobic silica "Cabosil (registered trademark) TS720" (manufactured by Cabot Japan Co., Ltd., hydrophobic treatment agent: dimethylsiloxane, average particle size: 12 μm) were placed in a Henschel mixer, stirred, and passed through a 150-mesh sieve to obtain a toner. The physical properties of the toner particles are shown in Table 7.
[0159] Examples B10 and B11 and Comparative Examples B5 and B6 100 parts by weight of binder resin, 4 parts by weight of colorant "Mogul-L" (Cabot Corporation), 0.2 parts by weight of Cyanine Blue 4927 (Dainichiseika Color & Chemicals Mfg. Co., Ltd.), 1 part by weight of charge control agent "T-77" (Hodogaya Chemical Co., Ltd.), and 3 parts by weight of release agent "Carnauba Wax C1" (Kato Yoko Co., Ltd., melting point: 80°C) were thoroughly mixed in a Henschel mixer and then melt-kneaded using a co-rotating twin-screw extruder with a total length of 1560 mm, a screw diameter of 42 mm, and a barrel inner diameter of 43 mm. The roll rotation speed was 200 r / min, the heating temperature inside the roll was set to 90°C, the temperature of the kneaded material was 140°C, the kneaded material was fed at a rate of 10 kg / h, and the average residence time was approximately 18 seconds. The obtained kneaded product was cooled from 140°C to 50°C in 1.5 hours, rolled and cooled at 50°C with a cooling roller, and then allowed to stand at 45°C for 4 hours. Thereafter, the product was pulverized in a jet mill and classified to obtain the volume median particle size (D 50 ) toner particles were obtained.
[0160] To 100 parts by mass of the obtained toner particles, 1.2 parts by mass of "Aerosil R-972" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle diameter: 16 nm) and 1.4 parts by mass of "RY-50" (hydrophobic silica, manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle diameter: 40 nm) were added as external additives, and the mixture was mixed in a Henschel mixer at 3600 r / min for 5 minutes to perform external addition treatment and obtain a toner.
[0161] Test Example 1 [Low temperature fixability] The toner was loaded into a copy machine "AR-505" (manufactured by Sharp Corporation) whose fixing unit was modified to enable fixing outside the machine, and a printout was obtained in an unfixed state (print area: 2 cm × 12 cm, adhesion amount: 0.5 mg / cm 2). Then, using a fixing machine (fixing speed: 300 mm / sec) adjusted to a total fixing pressure of 40 kgf, the temperature of the fixing roll was raised in 5°C increments from 100°C to 240°C, and a fixing test was conducted on the unfixed print at each temperature. Cellophane adhesive tape "UNICEF Cellophane" (Mitsubishi Pencil Co., Ltd., width: 18 mm, JIS Z1522:2009) was applied to the image area of the resulting print. The print was then passed through a fixing roller set at 30°C, separate from the fixing roll of the fixing machine, and the tape was then peeled off. The optical reflection density before and after tape application was measured using a reflection densitometer "RD-915" (Gretag Macbeth). The temperature of the fixing roll at which the ratio (after peeling / before application x 100) first exceeded 90% was defined as the minimum fixing temperature. The results are shown in Tables 7 and 8. The lower the minimum fixing temperature, the better the low-temperature fixability. The fixing paper used was "CopyBond SF-70NA" (manufactured by Sharp Corporation, 75 g / m 2 ) was used.
[0162] Test Example 2 [Hot Offset Resistance] In Test Example 1, the occurrence of hot offset at each fixing temperature was visually observed, and the lowest temperature at which hot offset occurred (hot offset occurrence temperature) was used as an index of hot offset resistance. The results are shown in Tables 7 and 8. The higher the lowest temperature at which hot offset occurred, the better the hot offset resistance.
[0163] In Comparative Example B5, hot offset occurred before the minimum fixing temperature was reached, and therefore proper fixing was not observed over the entire temperature range.
[0164] [Table 7]
[0165] [Table 8]
[0166] From the above results, it can be seen that the toners of Examples B1 to B11 containing the binder resin obtained by the method of the present invention are superior in both low temperature fixability and hot offset resistance, in comparison with Comparative Examples B1 to B6. In contrast, Comparative Example B1, which uses a binder resin with too little polymer (A), lacks hot offset resistance, and Comparative Example B5 does not achieve proper fixing over the entire temperature range.Furthermore, Comparative Examples B2 and B6, which use a binder resin with too much polymer (A), lack low-temperature fixing ability. Furthermore, a comparison between Comparative Examples B3 and B4 reveals that the hot offset resistance is insufficient in polyester resins that do not use addition polymerizable monomers and are not compounded, regardless of the presence or absence of polymer (A). [Industrial Applicability]
[0167] The binder resin for toner obtained by the method of the present invention is suitably used as a binder resin for toner for developing electrostatic images, which is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing, etc.
Claims
1. A method for producing a binder resin for toner, in which a polycondensation resin segment and an addition polymerization resin segment are bonded via a bireactive monomer, comprising: a step A of addition-polymerizing an addition-polymerizable monomer and a bireactive monomer in the presence of a polymer (A) having an unsaturated bond; and a step B of polycondensing a polycondensation monomer containing a carboxylic acid component and an alcohol component, the steps A and B being carried out in the same reaction vessel, wherein the amount of the monomer having an unsaturated bond constituting the polymer (A) having an unsaturated bond is 5.0×10 relative to 1 g of the total amount of the addition-polymerizable monomer, the bireactive monomer, and the polycondensation monomer. -5 mmol or more 2.0×10 -2 A method for producing a binder resin for toner having a molecular weight of less than 1 mmol.
2. 2. The process according to claim 1, wherein the weight average molecular weight of the polymer (A) having an unsaturated bond is 1,000 or more and 1,000,000 or less.
3. 2. The method according to claim 1, wherein the amount of the polymer (A) having an unsaturated bond used in step A is 0.01 parts by mass or more and 2.8 parts by mass or less per 100 parts by mass of the total amount of the polycondensation resin segment and the addition polymerization resin segment.
4. 2. The process according to claim 1, wherein the polymer (A) having an unsaturated bond is a polyester resin or a composite resin having a polyester resin segment and a styrene-based resin segment.
5. 2. The process according to claim 1, wherein the polymer (A) having an unsaturated bond has a structural unit derived from at least one of fumaric acid and maleic acid.
6. A method for producing a toner for developing an electrostatic image, comprising: a step (I) of dispersing the toner binder resin obtained by the method according to any one of claims 1 to 5 in an aqueous medium to obtain resin particles; and a step (II) of aggregating and fusing the resin particles to obtain toner particles.